Mapping Historical, Material and Affective entanglements in a Sami woman's discriminatory experiences in and beyond finnish boarding school - Tuija Huuki; Sandra Juutilainen (University of Aberdeen, School of Education, 2016)
This paper draws on new feminist materialist and posthuman theories to explore discrimination experienced by Sámi attendees at Finnish boarding schools. The aim is to shift attention away from the human actor to a wider field of power relations, and consider discrimination as force relations, emerging dynamically through assemblages of, for example, material, corporeal, historical, organic, discursive and affective elements. The case study, taken from the structured interview survey data from one Sámi woman, is used to demonstrate material, affective and historical forces, through which events of discrimination emerge. We argue that material objects and places and their histories are not inert, fixed backgrounds against which things occur, nor important contextualising features of situated events. Rather, they can be seen as significant actants in the rendering of the Sámi as the Other. Recognising how traces of place and history and material objects become revitalised within acting assemblages can provide some powerful insights into the barriers and opportunities the Sámi boarding school students encountered in their everyday lives and how they coped with experiences later in life.